2019
DOI: 10.1037/pag0000272
|View full text |Cite
|
Sign up to set email alerts
|

Aging effects on symbolic number comparison: No deceleration of numerical information retrieval but more conservative decision-making.

Abstract: Whereas many cognitive tasks show pronounced aging effects, even in healthy older adults, other tasks seem more resilient to aging. A small number of recent studies suggests that number comparison is possibly one of the abilities that remain unaltered across the life span. We investigated the ability to compare single-digit numbers in young (19-39 years; n = 39) and healthy older (65-79 years; n = 39) adults in considerable detail, analyzing accuracy as well as mean and variance of their response time, togethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 82 publications
2
9
1
Order By: Relevance
“…The linear model fit data from the B/Y task better than the log model and the log model fit data from the L/R task about the same as the linear model, except for the 70–90-year-old adults, for whom the linear model fit a little better. For both models, older adults had wider boundaries and longer nondecision times than young adults, results that have been obtained in many other experiments (e.g., Ratcliff, Thapar, Gomez et al, 2004; Ratcliff, Thapar, & McKoon, 2001, 2003, 2004, 2010, 2011; Reike & Schwarz, 2019; Spaniol, Madden, & Voss, 2006). Wider boundaries mean that older adults required more information before making decisions than young adults.…”
Section: Discussionsupporting
confidence: 76%
“…The linear model fit data from the B/Y task better than the log model and the log model fit data from the L/R task about the same as the linear model, except for the 70–90-year-old adults, for whom the linear model fit a little better. For both models, older adults had wider boundaries and longer nondecision times than young adults, results that have been obtained in many other experiments (e.g., Ratcliff, Thapar, Gomez et al, 2004; Ratcliff, Thapar, & McKoon, 2001, 2003, 2004, 2010, 2011; Reike & Schwarz, 2019; Spaniol, Madden, & Voss, 2006). Wider boundaries mean that older adults required more information before making decisions than young adults.…”
Section: Discussionsupporting
confidence: 76%
“…Similarly, the distance effect in single-digit number comparison was shown to be larger regarding speed but smaller regarding accuracy for older as compared to younger adults (Norris et al, 2015;Reike & Schwarz, 2019). From this, it can be concluded that number magnitude processing becomes more precise with lifetime experience during aging, but the processing speed in general decreases.…”
Section: Age-related Changes Over the Lifespanmentioning
confidence: 84%
“…For example, Hübner and Töbel (2019) and Wühr and Heuer (2018) modeled the nondecisional time as a constant, providing estimates of its value ranging from 100-350 ms. Similarly, analogous nondecisional times of diffusion models are often estimated to be 300-500 milliseconds in mean length (e.g., Ratcliff, 1978;Reike & Schwarz, 2019a;Schwarz & Reike, 2020;Voss et al, 2004). Modeling these times as a constant seems somewhat problematic, however, because it seems unlikely that a mental process consuming that much time on average would have negligible variance.…”
Section: Discussionmentioning
confidence: 99%